2020
DOI: 10.3390/brainsci10110893
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning Strategies to Enhance Neural Stem Cell-Based Therapy for Ischemic Stroke

Abstract: Transplantation of neural stem cells (NSCs) has been proposed as an alternative novel therapy to replace damaged neural circuitry after ischemic stroke onset. Nonetheless, albeit the potential of these cells for stroke therapy, many critical challenges are yet to be overcome to reach clinical applications. The major limitation of the NSC-based therapy is its inability to retain most of the donor stem cells after grafting into an ischemic brain area which is lacking of essential oxygen and nutrients for the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Minocycline preconditioning increases Nrf2 expression and neuroprotective paracrine secretion. It promotes migration, proliferation, and differentiation of NSCs to improve neurological recovery after NSC transplantation[ 220 , 221 ]. The molecular mechanism involves upregulation of antioxidant genes and reduced oxidative stress grafted cell death following transplantation, resulting in low-rate cell death[ 221 ].…”
Section: Strategies To Promote Stem Cell Survival For Transplantation Therapymentioning
confidence: 99%
“…Minocycline preconditioning increases Nrf2 expression and neuroprotective paracrine secretion. It promotes migration, proliferation, and differentiation of NSCs to improve neurological recovery after NSC transplantation[ 220 , 221 ]. The molecular mechanism involves upregulation of antioxidant genes and reduced oxidative stress grafted cell death following transplantation, resulting in low-rate cell death[ 221 ].…”
Section: Strategies To Promote Stem Cell Survival For Transplantation Therapymentioning
confidence: 99%
“…We did not investigate possible mechanisms underlying the effects of nicorandil. It was suggested to play an important role in neuroprotection after stroke by activating the PI3K/Akt signaling pathway [ 44 , 45 ], which remains further explored.…”
Section: Discussionmentioning
confidence: 99%
“…IS accounts for 70-90% of the incidence of strokes ( 1 ). It can cause irreversible neuronal damage in the ischemic area within a few minutes ( 2 ). Furthermore, studies indicated that IS is also the second leading cause of preventable deaths and the third leading cause of long-term disability among adults worldwide ( 3 ).…”
Section: Introductionmentioning
confidence: 99%